Entrepreneurial Literacy Development Program for Generation Z Student of Madrasah Aliyah: Program Pengembangan Literasi Kewirausahaan Pada Generasi Z Siswa Madrasah Aliyah - Ananta Hagabean; Andika Nuraga Budiman; Raousydiy Raousydiy (Journal of Entrepreneurship and Community Innovations, 2023)
In recent years, Indonesia's population is dominated by young people and most of them are Muslim. However, this condition is inversely proportional to the low level of entrepreneurial literacy in Indonesia. Thus, there is a need for early education in the younger generation who are studying high school or equivalent. The purpose of this activity is to introduce entrepreneurial skills and provide understanding to Generation Z students of MAN 3 Jakarta. In fact, this workshop will use video media, presentations and modules related to entrepreneurship to educate and foster the entrepreneurial spirit of MAN 3 Jakarta students. The results of this activity indicated that after the workshop, the number of students who were motivated to become young Muslim entrepreneurs had increased. Moreover, their passion and self-confidence, business ideas, and business conceptual ability also increased significantly after workshop. This event had strongly impact to increase the entrepreneurial intention among Madrasah Aliyah students. Therefore, this entrepreneurship education workshop needs to be developed and implemented on a large scale, not only for high school students, but the millennial generation in general.